2019
DOI: 10.1002/crat.201900053
|View full text |Cite
|
Sign up to set email alerts
|

Erlangen—An Important Center of Crystal Growth and Epitaxy: Major Scientific Results and Technological Solutions of the Last Four Decades

Abstract: This article describes the historic development of the Erlangen Crystal GrowthLaboratory CGL from its beginnings in 1974 at the chair of Materials of Electrical Engineering (Department of Material Science) of the University of Erlangen-Nuremberg until its current status as a large department "Materials" of the Erlangen Fraunhofer-Institute for Integrated Systems and Device Technology. Essential developments and scientific achievements in the various fields of crystal growth and epitaxy are presented from the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 218 publications
(242 reference statements)
0
1
0
Order By: Relevance
“…In this installation, even despite the low growth rate of the VGF process, it was possible to implement a highly profitable industrial process [2]. However, these achievements are inextricably linked with an increase in the chemical purity of the starting material to a purity of 7-8N [3][4][5]. Semiconductor crystals of cadmium telluride (CdTe) and its solid solutions (CdxZn1-xTe) are the best materials for room-temperature X-ray and gamma-ray detection systems [6], which are widely used in medicine, security systems, and scientific technology.…”
Section: Introductionmentioning
confidence: 98%
“…In this installation, even despite the low growth rate of the VGF process, it was possible to implement a highly profitable industrial process [2]. However, these achievements are inextricably linked with an increase in the chemical purity of the starting material to a purity of 7-8N [3][4][5]. Semiconductor crystals of cadmium telluride (CdTe) and its solid solutions (CdxZn1-xTe) are the best materials for room-temperature X-ray and gamma-ray detection systems [6], which are widely used in medicine, security systems, and scientific technology.…”
Section: Introductionmentioning
confidence: 98%
“…In this installation, despite the low growth rate of the VGF process, it was possible to implement a highly profitable industrial process [2]. However, these achievements are inextricably linked with an increase in the chemical purity of the starting material to a purity of 7-8N [3][4][5]. Semiconductor crystals of cadmium telluride (CdTe) and its solid solutions (CdxZn1-xTe) are the best materials for room-temperature X-ray and gamma-ray detection systems [7], which are widely used in medicine, security systems, and scientific technology.…”
Section: Introductionmentioning
confidence: 99%
“…Stefanescu et al [143] measured the critical velocity under microgravity conditions and obtained a conclusion similar to that of Sen et al [142]. The freezing process of silicon with SiC particles was investigated by Friedrich et al [144] and Friedrich and Müller [145], and they found a lower critical velocity under microgravity conditions. This phenomenon is caused by the reduced natural convection, which leads to a decrease in the lift force on the particles under microgravity conditions.…”
mentioning
confidence: 61%